Satellite internet technology implementation for the practice of medicine and surgery - Nahm, William J.; Boyd, Carter J.; Montgomery, Robert A. (The American journal of surgery, 2023)
[...]the Ukrainian populace and military can now access high-speed internet from SpaceX's satellite internet service, Starlink, which comprises numerous low Earth orbit satellites.1 Such an example demonstrates how satellite technology can provide internet support anywhere in the world, no matter the state of an area's infrastructure. Before the more ubiquitous implementation of satellite technology in Ukraine at the start of the war, members of our institution covertly had to travel there to train Ukrainian transplant surgeons. [...]only after satellite technology was implemented were we able to allow Ukrainian surgeons to participate in a United States (US) based surgical meeting and engage in telementoring. All these traditional internet routes are subject to interruption during natural disasters or intentional physical attacks. [...]they are subject to cyberattacks through regional modulation or political or government control. Because it relies on a line of sight, usage in canyons or areas with tall tree lines can be a problem.